2006
DOI: 10.1152/physiolgenomics.00244.2005
|View full text |Cite
|
Sign up to set email alerts
|

A second expressed kininogen gene in mice

Abstract: . A second expressed kininogen gene in mice. Physiol Genomics 26: 152-157, 2006; doi:10.1152/physiolgenomics.00244.2005.-We isolated PCR, RNA ligase-mediated rapid amplification of cDNA ends (RLM-RACE-PCR)-, and RT-PCR-generated clones from mouse kininogen family transcripts. DNA sequencing indicated that the clones were from two distinct genes. One set (K1) is from the previously reported mouse kininogen gene. The second set (K2) has an open reading frame, is 93% identical to K1 in the overlapping nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Our results are consistent with these findings, though Shesely et al did not assess the roles of the 2 kininogen genes in production of kininogen protein. 31 In our studies, deletion of mKng1 was confirmed by demonstrating the absence of mKng1-derived mRNA in tissues in which the gene is normally expressed (Figure 5). Deletion of this gene allowed us to analyze the contribution of the 2 kininogen genes to the production of plasma kininogen.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our results are consistent with these findings, though Shesely et al did not assess the roles of the 2 kininogen genes in production of kininogen protein. 31 In our studies, deletion of mKng1 was confirmed by demonstrating the absence of mKng1-derived mRNA in tissues in which the gene is normally expressed (Figure 5). Deletion of this gene allowed us to analyze the contribution of the 2 kininogen genes to the production of plasma kininogen.…”
Section: Discussionsupporting
confidence: 65%
“…31 These investigators reported mKng1-derived HK and LK mRNA and mKng2-derived LK mRNA in the liver, and mKng1-derived LK and mKng2-derived For personal use only. on June 19, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Humans have one kininogen gene; rodents have two closely linked kininogen genes. 22 Kallidin can be converted into bradykinin by a plasma aminopeptidase. All the kinins are strong agonists of the bradykinin 2 receptor (B2R, Bdkrb2), although less so of the B1 receptor (B1R, Bdkrb1).…”
Section: Introductionmentioning
confidence: 99%